Renewal of the Soul According to Sheikh Hamza Yusuf (1958-2025) - Yaqin, Alifia Haqqul; Azani, Mohammad Zakki (JUSPI (Jurnal Sejarah Peradaban Islam), 2025)
Education is a fundamental aspect of shaping the human personality as a whole, including the soul, which serves as the center of consciousness and morality. This study aims to describe the concept of soul education as well as other aspects of soul renewal found in The Agenda of Soul Renewal by Sheikh Hamza Yusuf (January 1, 1958). This research employs a qualitative descriptive method using library research. The main data source is the book Agenda of Soul Renewal, supported by relevant books and journals. The findings indicate that the agenda not only presents soul education as a process of purification and personal development but also elaborates a broader concept of soul renewal, including introspection, spiritual reform, and strengthening social roles. According to Sheikh Hamza Yusuf, soul renewal encompasses moral, emotional, and social dimensions that are interconnected in shaping a holistic human being. Besides internal obstacles such as egoism and unsupportive environments, the agenda emphasizes practical improvement steps through the implementation of Islamic values such as the pillars of faith and Islam, virtuous character, da'wah, charity, remembrance (dhikr), and empathy.